2016
DOI: 10.22487/j24428744.2016.v2.i2.5977
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH GEL EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) TERHADAP PENYEMBUHAN LUKA BAKAR PADA KELINCI (Oryctolagus cuniculus)

Abstract: Research on Gel Formulation of red betel leaf extract (Piper crocatum Ruiz & Pav) for the treatment of burn wounds in rabbits (Oryctolagus cuniculus) has been conducted. This study aimed to determine variation’s effect of concentration in gel of red betel leaf extract for the treatment of burn wounds in rabbits which had been wounded using hot metal. In this study, the viscous extract was formulated into gel with concentrations of 1%, 2% and 3%. The Gel’s Physical quality evaluation included organoleptic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
0
4
0
12
Order By: Relevance
“…Yield calculations were carried out with 16.96 g sample weight, and it was found that the percentage yield was 6.78%. In contrast, Ulviani et al (2016) obtained the red betel leaf extract yield of 6.14%. This is different from several studies which obtained higher extract yields of 13.59% each.…”
Section: Red Betel Leaf Extractionmentioning
confidence: 82%
“…Yield calculations were carried out with 16.96 g sample weight, and it was found that the percentage yield was 6.78%. In contrast, Ulviani et al (2016) obtained the red betel leaf extract yield of 6.14%. This is different from several studies which obtained higher extract yields of 13.59% each.…”
Section: Red Betel Leaf Extractionmentioning
confidence: 82%
“…Pemberian sediaan topikal yang tepat dan efektif diharapkan dapat mengurangi dan mencegah infeksi pada luka (Rismana et al, 2013). Bentuk sediaan topikal yang dapat dengan mudah digunakan untuk pengobatan pada luka salah satunya adalah sediaan gel merupakan sediaan yang memiliki daya sebar yang baik diantara sediaan topikal lainnya sehingga lebih mudah untuk dioleskan pada luka (Ulviani, 2016).…”
Section: Pendahuluanunclassified
“…Setelah penambahan ekstrak daun singkong gel 40% memiliki pH 6,4, gel 50% pH memiliki 6,3 dan gel 60% memiliki pH yaitu 5,8. Sediaan yang dibuat memenuhi kriteria pH untuk sediaan kulit karena berada di interval 4,0-6,8 yang masih berada pada kisaran pH kulit sehingga sediaan gel ini aman untuk digunakan (Ulviani, 2016). Gel yang bersifat terlalu asam akan mengiritasi kulit sedangkan gel yang terlalu basa akan membuat kulit menjadi bersisik (Sugiyono, 2009).…”
Section: Tabel 4 Uji Phunclassified
See 1 more Smart Citation
“…Berdasarkan beberapa penelitian yang telah dilakukan sebelumnya, banyak penelitian yang membahas mengenai kandungan fraksi aktif methanol daun sirih hijau (Hafida, Ekiyantini, & Sri, 2012;Haryun, WIdodo, & Sudjarwo, 2017;Moch, 2014;Syahrinastiti, A, Aziz, & Lili, 2015;Ulviani, Yusriadi, & Khaerati, 2016;Widjaya, Retnani, & Hermana, 2018;Wilis & Andriani, 2017) Serta penelitian mengenai antibakteri Salmonella typhi (Moch, 2014;Nirwana, 2013;Nita, 2013). Namun, belum adanya penelitian yang mengembangkan lembar aktivis matematika berorientasi pendekatan saintifik untuk siswa SD Berdasarkan kajian terdahulu keterbaruan penelitian ini terletak pada efektivitas dan kandungan fraksi aktif methanol daun sirih hijau sebagai antibakteri Salmonella typhi.…”
unclassified